Anti-quorum sensing activity of Pistacia atlantica against Pseudomonas aeruginosa PAO1 and identification of its bioactive compounds. (September 2017) - Kordbacheh, H.; Eftekhar, F.; Ebrahimi, S.N.
Abstract: Pseudomonas aeruginosa is a multidrug resistant opportunistic pathogen and an important cause of nosocomial infections. Quorum-sensing (QS) is a process in which bacterial cell-cell communication can regulates production of many virulence factors including pigment formation and the ability to form biofilm which is essential for establishment of chronic infections. We examined the inhibitory effect of Pistacia atlantica ( Anacardiaceae ) methanolic leaf extract and its bioactive components on biofilm formation and pigment production by P. aeruginosa PAO1. Fractionation of the methanolic leaf extract was carried out using HPLC based activity profiling. Identification of the active compounds was carried out by the integrated approach of HPLC-DAD and LC-MS followed by molecular docking analysis. Pistacia atlantica crude extract at 2 and 1 mg/mL, inhibited 92% and 79% biofilm formation, respectively. Minimum biofilm inhibitory concentration (MBIC) determined by microbroth dilution was 0.25 mg/mL with 39% inhibition. Pyocyanin production measured by spectrophotometry showed 100% and 83% inhibition at 2 and 1 mg/mL and minimum inhibitory concentration (MIC) was 0.5 mg/mL with 40% inhibition. Four active HPLC fractions (11, 15, 16 and 19) showed MBIC values of 0.06, 0.16, 0.10, 0.15 mg/mL, and MICs for pyocyanin production of 0.49, 0.31, 0.76, >0.30 mg/mL, respectively. The active compounds were identified as rutin (1 ), myricetin, 3- O -rutinoside (2 ) and kaempferol-3- O -rutinoside (4 ), all belonging to the flavonoid family. Molecular docking simulation of the active compounds showed that all had high affinity for LasR protein which is an important quorum-sensing signal receptor. The results of this study suggest that the active components of P. atlantica have high anti -QS activities and may have the potential for treatment of chronic infections caused by Pseudomonas aeruginosa . Highlights: Fractionation of the methanolic leaf extract was carried out using HPLC based activity profiling. Minimum Biofilm Inhibitory Concentration (MBIC).